Non-carcinogenic health risks assessment of bioaerosols. - Azhar Siddique; Kashif Rasool (MethodsX, 2025)
Bioaerosols, pose potential health risks, yet quantitative assessments of non-carcinogenic risks from bioaerosol inhalation are limited. This study introduces a novel approach for assessing non-carcinogenic health risks using bioaerosol exposure data. The method employs the Average Daily Dose and Hazard Quotient (HQ) metrics, adapted from US Environmental Protection Agency guidelines, with the Reference Dose (RfD) based on thresholds from the National Institute of Occupational Safety and Health and the American Conference of Governmental Industrial Hygienists. This study utilizes a time-weighted approach, considering age-specific inhalation rates and body weights, to enhance the precision of lifetime exposure assessments. This methodology was applied to data collected over one year across multiple locations in Qatar, assessing seasonal and site-specific variations in risk. Results indicate generally low health risks, with HQ values below 1 for most sites and seasons. However, the study identified elevated HQ values at highly active sites during the dry summer, suggesting potential health concerns that need urgent attention. The proposed framework offers a replicable approach for evaluating bioaerosol-related health risks across diverse environments. • Novel adaptation of HQ-based risk assessment for bioaerosols in Qatar, incorporating a time-weighted approach. • Evaluation of seasonal and site-specific exposure dynamics. • Designed for replicability in different environmental conditions.